Pierādīšanas problēmas lietās par administratīvajiem pārkāpumiem ceļu satiksmē. - Kokoreviča, Jolanta (Latvijas Universitāte, 2011)
The aim of the Bachelor paper "Problems of proof in cases of administrative violations in road traffic" is to make a research about the evidences and proofs in the administrative violation cases in road traffic of the regulatory gaps and problems encountered in practice, and also to provide proposals for improvements and preclusion of incompleteness. The paper analyzes the instruments of evidences, which application in the cases of administrative violations in traffic, are regulated by the Latvian Administrative Violations Code. As the result the conclusions about the procedural regulation of evidences and about the methods applied have been drawn out and proposals of their preclusion have been provided. Simultaneously, the author concluded that in the administrative violation cases, where the initial decision is adopted by the authority of an impartial investigation, the principle of objective investigation, which determines the Court to participate in the process of evidence collecting, is acting. By the contrast, in cases where the initial decision is adopted by the Court of Law, institution’s operations in the collecting of evidences are limited. Finally, it was concluded that the reasons for which it is often impossible to prove the administrative violation done by the person, are connected not only with the improvements of procedural rules, but also with the following: in the administrative violation cases, in which the decision is adopted by the general Court of Law, one of the subjects involved in the process is missing. Namely, the person who guides the proceedings, collects evidences and ensures the function of accusation.
Problems of evidence in cases of administrative violation of road traffic.
Keywords: Juridiskā zinātne